Alimentação de suínos em terminação com dietas contendo ractopamina e extratos cítricos: desempenho, características de carcaça, da carne e produto curado - Rossi, Carlos Augusto Rigon (2010)
This study evaluated the effects of addition of ractopamine and citrus extracts in the diets of finishing pigs on performance, characteristics of carcass, meat and cured product. Hundred eight pigs were used (54 males and 54 females) in a completely randomized design, blocked by sex with nine treatments: T1 - control (C) (0 ppm of ractopamine e 0 ppm of citrus extracts), T2 - C + 10 RAC (RAC: ractopamine, ppm), T3 - C + 20 RAC, T4. C + 250 EC (EC: citrus extracts, ppm), T5 - C + 500 EC, T6 - C + 250 EC + 10 RAC, T7 - C + 250 EC + 20 RAC, T8 - C + 500 EC + 10 RAC e T9 - C + 500 EC + 20 RAC. Two sexes were used, with four replicates and three animals per experimental unit, with repetition over time. The performance of animals was not affected (P>0.05) by treatments. The backfat thickness of the control was 35% higher (P<0.05) to levels of RAC and 10 RAC + 500 EC. The lean meat of the control was 5.3% lower (P<0.05) compared to levels of ractopamine. The protein content of the Longissimus dorsi for the inclusion of 20 RAC was 5.5% higher (P<0.05) to two EC levels in the diet. The moisture of muscle samples from the animals that received 20 RAC and 500 EC was 4.3% higher (P<0.05) to control and 500 EC. The levels of linoleic acid in Longissimus dorsi muscle for the group 10 RAC + 500 EC was 18% higher (P<0.05) compared to 500 EC. The levels of α-linolenic acid of the control was 33.5% higher (P<0.05) to levels RAC, EC and their associations. The concentration of arachidonic acid of the interaction 20 RAC + 250 EC was 36% higher (P<0.05) for the concentrations of 20 RAC. The protein content in the salami from the treatments with 250 and 10 RAC + 500 EC, was on average 25% higher (P<0.05) to control. The fat content of salami for the control was 16% higher (P<0.05) compared to other treatments. In sensory analisys the color of salami made with meat from the females for the level of inclusion 10 RAC + 250 EC, the acceptability was better (P<0.05) compared to other treatments. In relation to the characteristic odor, the salami prepared with meat of females from group 500 EC, the acceptability was better (P<0.05) compared to other treatments. The flavor of salami made with meat from the males and females of treatment with 500 EC, the acceptability was better (P<0.05) compared to other treatments. The texture of the salami made with meat from males and females of treatment with 20 RAC + 250 EC, the acceptability was better (P<0.05) compared to other treatments. The performance of animals was not altered by the treatments. The ractopamine in the diet of finishing pigs decreases the thickness of backfat. The treatment with 20 ppm of ractopamine increases weight in the carcass. The percentage of lean meat is influenced by the treatments. The ractopamine in the diet, compared to citrus extracts, increases the protein content in the Longissimus dorsi. The extracts citrus influence positively the levels of the fatty acid lauric. The interaction with 10 RAC + 500 EC increases the levels of linoleic acid. Linolenic acid is negatively influenced by the levels of ractopamine, citrus extracts and their associations. The interaction with 10 RAC + 250 EC increase the concentration of arachidonic acid. The salami made with meat the animals with addition of ractopamine and citrus extracts in the diet does not affect the count of Coliforms, Staphylococcus and Salmonella spp, but reduces the count of bacterial lácticas. O salami made with meat from animals that received addition of ractopamine and citrus extracts in the diet had higher protein levels and lipid content. The salami made with meat from animals that received the addition of 500 ppm of citric extracts in the diet, the acceptability was better by sensory analysis.